Comparative Study of Aflatoxin M1 Carry-Over from Feed to Raw ‎Milk in Cow, Buffalo, Sheep, and Goats in Different Areas of ‎Baghdad Province - Al-Rubaye, Hasan; Atiyah, Adil J; Huang, Shuai (The Iraqi Journal of Veterinary Medicine, 2023)
Mycotoxin aflatoxin B1 (AFB1) is a threat to food safety and human health because it is present in animal feed and is metabolized into aflatoxin M1 (AFM1), a more toxic form, during lactation. The aim of this study was to quantify AFM1 concentrations in raw milk of buffalos, cows, sheep, and goats sampled randomly from four regions within Baghdad ‎Province, Iraq, and to compare these levels with the maximum allowable levels set forth by the ‎European Commission (EC), the Iraqi Standard Specification (IQS), and the food and Drug Administration (FDA). The carry-over of AFB1 from feed to AFM1 in milk were also calculated for each of the ‎studied species. A total of 200 random samples, including 50 each from cows, buffaloes, ‎sheep, and goats, were collected from farms located in Zu'afraniya, Nahrawan, Abu Ghraib, and ‎Fedhalia regions. AFM1 and AFB1 concentrations were determined using the ‎enzyme-linked immunosorbent assay (ELISA). Raw milk samples from cows, sheep, buffaloes, and goats were all found to have AFM1 concentrations that were below the limits set by the EC, IQS, and FDA. Animal feed samples, on the other hand, had AFB1 concentrations of 10.08, 5.95, 4.27, and 7.10 ppb for ‎buffaloes, cows, sheep, and goats, respectively. The observed carry-over rates ranged from 0.36% ‎in goats to 0.78% in buffaloes to 0.66% in cows. Multiple factors, including animal species, ‎are considered, and it is determined that a universal carry-over equation cannot be applied to all cases. ‎Therefore, it is essential to regularly monitor AFM1 levels in milk from various animal species in order to ‎lessen potential health risks. Furthermore, the study suggests enhancing agricultural and veterinary ‎practices to better regulate feed quality for dairy animals‎‎‎‎.